Pengaruh Inflasi dan Suku Bunga Terhadap Return on Asset Bank yang Listing pada BEI - Rafiuddin Rafiuddin (Jurnal Akademik FKIP Unidayan, 2019)
This research was conducted to find out and to analyze the influence of interest rate toward the Return on Asset Bank that list on BEI period 2014-2016. This research was a quantitative descriptive, the data was analyzed by using time series and it used multiple linear Regression. The result obtained the equation Y = -0,114 + 0,609X1 + 0,967X2, it showed a directional correlation between inflation and interest rate toward ROA. Coefficient of determination showed the inflation and the interest rate have contribution toward ROA was 13,6%. The result of t-test also showed that, the inflation and interest rate variables have no significant influence toward ROA. Whereas, F test showed the inflation and interest rate have significant influence toward ROA